(3TQM GdeUHGMs - (3eLghds
(3ChdgG (B:s
(3Ef CMb eG jJhTM HPcQg UOhQ GdcJH hGdOaGJQ MeO Gddg JYGdi CeG HYO aEf fhY GdCOH Ydi cKQg TLhfg fhY JCHi Ydi GdWdHI eQGeg hcJHJ ai TQM GdeUHGM cJGHkG LeYJ ajg ef GdahGFO s
(3BNQgG (B:s
(3hGddg CYde HGdUhGH , hEdjg GdeQLY hGdeBH fbeg GdYHO GdVYja MSf Gdbhfhi ai TgQPi GdMLI SfI KeGf hKdGKjf hSHYeGFI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B71 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B488s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdfMhs